Markhasphingolipid A, new phytosphingolipid from the leaves of Markhamia stipulata var. canaense V.S. Dang. Issue 13 (2nd July 2020) - Ngo, Trong Nghia; Nguyen, Nu Dan Phuong; Nguyen, Ngoc Thien Ly; Pham, Nguyen Kim Tuyen; Phan, Nhat Minh; Bui, Trong Dat; Dang, Van Son; Tran, Cong Luan; Mai, Dinh Tri; Nguyen, Tan Phat
Abstract: From the leaves of Markhamia stipulata var. canaense V.S. Dang, one new phytosphingolipid, named markhasphingolipid A (6 ) together with five known compounds, 4', 7- O -dimethylapigenin (1 ), narigenin (2 ), tectoquinone (3 ), mollic acid (4 ), 1-hexadecanoyl- sn -glycerol (5) were classified by various chromatographic methods. Their structures were designated by IR, UV, HR-ESI-MS, HR-ESI-MS/MS and NMR experiments. All compounds were recognized for the first time from this species. The cytotoxicity of all n -hexane fractions and isolated compounds (5 & 6) against three human cancer cell lines (HeLa, HepG2, and MCF-7) were evaluated by SRB assay. All n -hexane fractions expressed cytotoxic effect on three tested cancer cell lines (at the concentration of 100 μg/mL, percent of cytotoxicity ranged from 55.81% to 95.83%) as well as compound 5 (IC50 ranged from 48.51 to 63.30 μM) whereas fraction H.I and compound 6 did not show activity.